“We Boil at Different Degrees”: Factors Associated With Severity of Attack in Sexual Killing - Stefanska, Ewa B. (Journal of interpersonal violence, 2021)
Degree of injury, as measured by the Homicide Injury Scale (HIS), was examined to advance understanding of the dynamics of sexual killing. A total of 350 nonserial, male sexual killers were included, and the different ways that the sexual element of their offenses and the act of killing were connected was accounted for by determining that cases were either directly sexual (the sexual element and killing were closely bound), or indirectly sexual (killing was not a source of sexual stimulation). The two groups, direct and indirect sexual killers, were each subjected to multiple linear regression analyses to examine the group-specific relationship between level of injury and predictor variables previously found to be associated with increased severity of attack. No differences in the mean total HIS scores between the indirect and the direct cases were found, suggesting a comparable emotional intensity between the groups. However, given that the groups differed in terms of the functional role of fatal violence, severity of attack could not be sufficiently explained as driven by anger. In line with this hypothesis, different predictors appeared to be associated with increased degree of injury sustained by victims of indirect compared with direct sexual killers. As such, situational components appear to play a role in the behavior of indirect sexual killers, whereas the behavior of direct perpetrators tends to be linked with the enactment of existing deviant fantasies. The role of anger in sexual homicide is discussed further, and overall, it is argued that irrespective of whether violence was initially driven by anger, evidence of sexual arousal to severe violence must be scrutinized within sexual homicide research as well as in psycholegal contexts.